ANALISIS TINGKAT LITERASI POLITIK MAHASISWA PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN FKIP UNIVERSITAS RIAU - Yaldi, Apri; Erlinda, Sri; ,, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The higher education environment is a strategic place to develop reading habits. However, in reality, this expectation has not yet been realized, as reading interest among students remains low. The implementation of discussion programs related to political, social, and cultural issues is still frequently conducted among students as one means to enhance knowledge. This is commonly done by students at any university, including students of the Pancasila and Citizenship Education Program at the Faculty of Education and Educational Sciences, University of Riau. However, not all students of the Pancasila and Citizenship Education Program at the Faculty of Education and Educational Sciences, University of Riau, are willing to participate in such activities. Based on the researcher's initial observations of students of the Pancasila and Citizenship Education Program at the Faculty of Education and Educational Sciences, University of Riau regarding political knowledge, all students are aware of political parties. However, many of them are not interested in politics and have never participated in demonstrations related to political issues. The reasons vary, some do not want to get involved, some do not understand the political world, some are not allowed to participate by their parents, and so on, which can affect their political participation. This study aims to determine the level of political literacy among PPKn FKIP University of Riau students. This study was conducted in the PPKn program at the Faculty of Education and Teacher Training, University of Riau. This is a descriptive quantitative study. The sample was selected using proportional sampling, with a total of 127 students. The results indicate that the political knowledge level of PPKn students at the Faculty of Education and Teacher Training, University of Riau, is 74%, political skill level is 76%, and political attitude level is 39%.Keywords: political literacy